Heritability of the timing of food intake. Issue 2 (April 2019) - Lopez-Minguez, Jesus; Dashti, Hassan S.; Madrid-Valero, Juan J.; Madrid, Juan A.; Saxena, Richa; Scheer, Frank A.J.L.; Ordoñana, Juan R.; Garaulet, Marta
Summary: Background & aims: While environmental factors are presumed to be primary drivers of food timing, preliminary evidence suggests that genetics may be an additional determinant. The aim was to explore the relative contribution of genetics and environmental factors to variation in the timing of food intake in a Spanish twin population. Because chronotype, bedtime and wake time are related to food timing, covariance with food timing was further assessed. Methods: In this observational study, 53 pairs of adult (mean (SD) = 52 (6.03) years) female twins (28 monozygotic; 25 dizygotic) were recruited from the Murcia Twin Register. Zygosity was determined by DNA-testing. Timing of the three main meals of the day was assessed via 7-day dietary records, and the midpoint of food intake was computed by calculating the midpoint between breakfast and dinner times. Chronotype, bedtime and wake time were self-reported. Heritability of food timing and related traits were estimated by comparing monozygotic and dizygotic twin correlations and fitting genetic structural equation models to measured variables. Results: We observed genetic influences for food timing, with highest heritability for the midpoint of food intake (64%) in an overweight/obese population (BMI = 26.01 ± 3.77). Genetic factors contributed to a higher degree to the timing of breakfast (56%) than the timing of lunch (38%) or dinner (n.s.). Similarly, heritability estimates were larger in related behavioral traits earlier on in the day (i.e. wake time, (55%)), than those later on in the day (i.e. bedtime, (38%)). Bivariate analyses revealed a significant genetic overlap between food timing and bedtime and chronotype (rG between 0.78 and 0.91). Conclusions: Genetic influences appear to account for a significant proportion of the variability in food timing, particularly breakfast. Thus, interventions related to food timing may be more effective when targeting afternoon/evening traits, such as lunch or dinner times. Furthermore, our data suggest shared genetic architecture underlying food timing and phenotypically related traits. Clinical trial: NCT03059576 .https://clinicaltrials.gov/ct2/show/NCT03059576 . Graphical abstract: Our study investigates the relative contribution of genetic and environmental factors to the timing of food timing and related behaviors. Our results show that the heritability of the midpoint of intake, the midpoint between breakfast and dinner, was 64%. In addition, trait heritability was higher for breakfast than lunch, whereas no heritability was detected for dinner. These results suggest that interventions related to food timing may be more effective when targeting afternoon/evening behaviors, such as lunch or dinner times. Highlights: Food timing is a novel dimension in nutrition. Indeed, food timing intake is newly proposed as a modifiable risk factor for weight management and chronic disease prevention. The present study provides supporting evidence that the timing of food intake has an underlying genetic component. Heritability plays a larger role in other behaviors specific to the morning, but the environmental component is larger for the timing of dinner. These findings have relevance to the prevention and treatment of metabolic disorders. These results suggest that modifiable factors later on in the day, such as lunch or dinner could be more effective, rather than breakfast.